PEMIKIRAN FILSUF DALAM PENDIDIKAN ISLAM: MENELUSURI WARISAN PEMIKIRAN DAN PRAKTIK (AL-BANNA, MUHAMMAD ABDUH, MOHAMMAD IQBAL, NAQUIB ALATTAS) - Sholikha, Riadhotus; Rosyad, Muh Sabilar (MIYAH : Jurnal Studi Islam, 2025)
This paper discusses the evolution of Islamic education, emphasizing the transformative role it plays in shaping the individual’s behavior, social interactions, and environmental context. The primary objective is to explore the contributions of influential Islamic thinkers, including Hasan Al-Banna, Muhammad Abduh, Mohammad Iqbal, and Naquib Al-Attas, to the development of Islamic educational paradigms. A descriptive and analytical approach is employed to examine their thoughts on the integration of Islamic principles with modern education. The findings reveal that these scholars advocated for education as a tool for moral and intellectual development, with a focus on fostering a balanced individual capable of contributing to society. Al-Banna emphasized character building, Abduh promoted critical thinking and the integration of religious and secular knowledge, Iqbal emphasized self-realization and independence, while Al-Attas highlighted the moral and spiritual dimensions of education. In conclusion, the study highlights that Islamic education, as envisioned by these thinkers, aims to produce individuals who are intellectually, morally, and spiritually equipped to face modern challenges while adhering to Islamic values.